The Role of Pesantren in Guarding the Islamic Moderation - Muh Hafidz (State Institute of Islamic Studies (IAIN) Salatiga, 2021)
The purpose of this study is to answer the research questions on how pesantren Al Ittihad guards the Islamic moderation inherited from the previous generation in this globalization era, what aspects of moderation are carried out and how to implement them. To answer these two research questions, the researcher used technique of data collection through interview, documentation and observation. Based on the results of documentation and interview with kyai, alumni and administrator of pesantren, it produced comprehensive information. After collecting the data, the researcher analyzes by steps, namely data reduction, data display, data verification and conclusions. There are two conclusions in this study. First, there are four types of programs run by pesantren Al Ittihad in guarding the Islamic moderation in Indonesia. First, the teaching of a classical book as a medium for the transformation of Islamic sciences. Second, the implementation of extra-educational activities and pesantren teaching in the form of speech, negotiation, ziarah kubur, yasinan, mujahadah, Al Barjanji, manaqib, and tahlil. Third, establishing formal school in the pesantren for santri and the community around it. Fourth, inviting government and community leaders who have moderate Islamic understanding. Second, the moderation carried out by pesantren Al Ittihad covers the fields of religious thought, education, Islamic rites, tolerance, politics, economics and tradition and culture